Research on Calibration Method of Laser Camera Sensor - LIU Shiwang; HU Yunqing; LIN Jun (Kongzhi Yu Xinxi Jishu)
Laser camera sensor calibration is a key work step for a visual inspection system, and accurate solution of calibration model parameters is the difficulty of laser camera sensor calibration. In this paper, a laser camera sensor calibration mathematical model was established, and the process of solving the calibration model parameters by the nonlinear least square method and Gauss-Newton iterative method was analyzed, and a L-M algorithm based on maximum likelihood estimation was proposed. The algorithm uses the maximum likelihood estimation to reduce the error caused by image noise, and then the L-M method is used to find the optimal solution for the calibration parameters. Then, it used a needle-shaped target-based motion calibration method for calibration experiments. For 800 sets of calibration data, the nonlinear least square method, Gauss-Newton iteration method and the L-M algorithm based on maximum likelihood estimation were used to solve the calibration model parameters; the other 1 000 sets of calibration data were taken for error analysis. Comprehensive analysis of the two sets of data shows that mean square error of the L-M algorithm based on maximum likelihood estimation is reduced by 0.221 4 mm and 0.212 3 mm respectively, and the calibration accuracy of this method is improved effectively.